How to Make Changes in Public Organization: Case Study in Bojonegoro Regency, 2008-2018 - Amanda Setiorini; Tuty Sariwulan; Saparuddin Mukhtar (Ridwan Institute, 2022)
In a public organization that is difficult to change, it turns out that the Bojonegoro district government can make various breakthroughs. This study aims to find out how they make changes. Using a case study approach, ten ways to make changes were found, namely communication, community empowerment, professionalism, building trust, financial management, being a mediator, understanding community culture/social/customs, synergizing, clear regulation, and walk-the-talk. These methods are not implemented separately but are interrelated to provide maximum impact for people who have a long history of endemic poverty. Some of the methods are related to the concepts of new public management and reinventing government, although the local government of Bojonegoro itself is not familiar with these concepts. By making the organization a learning organization, local governments that tend to be static will become more agile in carrying out their duties.